Measures of Efficiency and Investments return: an study of Brazilian electricity distributors with Data Envelopment Analysis, Malmquist Index and ROI - Saurin, Valter; Lopes, Ana Lúcia Miranda; Costa Júnior, Newton Carneiro A.; Gonçalves, Carlos Alberto (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346597845 This paper aims to determine, in a group of companies from the Brazilian electric sector, if there is a relationship between the return on investment (ROI) and the concept of efficiency estimated by the method Data Envelopment Analysis (DEA), as well as evaluating the growth of productivity based on Malmquist Index (Fare et al, 1996). The hypothesis is that firms that had return on investment higher during certain period of time are those employed their resources efficiently in getting their outputs (DEA efficient). The input (1) Products (5) DEA model correspond to the operating cost (I), the network length (km), the number of consumers and the market billed high, medium and low voltage, respectively. The sample consisted of 31 companies of Brazilian electricity distribution and timing of the study was from 2007 to 2009. We calculated the Malmquist index (M0), represented by the change in total factor productivity (TFPC), which is composed by the evolution of technical efficiency (EC) and the change in the technological frontier (TC) of the companies were also determined ROI for each period. We calculated the correlation between the TFPC, TC, EC, score the DEA and the ROI for the period 2007 to 2009. The results showed a positive correlation, although weak, between efficiency change and the indexes mentioned above, rejecting the initial hypothesis